The role of the neutrophil-to-lymphocyte ratio in avoiding negative appendectomies - Carlos Delgado-Miguel; Antonio Muñoz-Serrano; María San Basilio; Miriam Miguel-Ferrero; María de Ceano-Vivas; Leopoldo Martínez (Elsevier, 2023)
Introduction: The neutrophil-to-lymphocyte ratio (NLR) is an inflammatory biomarker that is easily calculated with data from the differential white blood cell count. The aim of our study was to analyse the role of the NLR in the detection of negative appendectomies and to compare its usefulness with other clinical, sonographic and laboratory factors previously described. Methods: We conducted a retrospective study in patients aged less than 16 years who underwent appendectomy in our hospital between 2017 and 2020. We divided patients into 2 groups based on appendiceal histological findings: NA group (negative appendicitis: absence of appendiceal inflammation) and PA group (positive appendicitis: presence of inflammation in any layer of the appendiceal wall). We analysed demographic, clinical, sonographic and laboratory characteristics. Results: We included a total of 1269 patients, 1244 in the PA group and 25 in the NA group, with no differences between groups in demographic characteristics. The proportion of patients that presented with nausea and vomiting was significantly smaller in the NA group compared to the PA group (P < .001), and there were no other differences in symptoms. The appendiceal diameter on ultrasound was significantly smaller in the NA group (8.1 ± 2.1 vs. 9.7 ± 2.8 mm; P < .001). The white blood cell and neutrophil counts and the NLR were significantly higher in the PA group (P < .001), as was the level of C-reactive protein (18.6 vs. 2.6; P = .005). The ROC curve analysis revealed that the NLR was the parameter with the highest AUC (0.879) for the diagnosis of negative appendicitis, with a cut-off point of 2.65 for a maximum sensitivity of 84.2% and specificity of 83.8%. Conclusion: The NLR is the preoperative parameter that best discriminates patients without acute appendicitis. Values of less than 2.65 should make clinicians contemplate diagnoses other than appendicitis. Resumen: Introducción: El índice neutrófilo-linfocito (INL) es un biomarcador inflamatorio fácilmente calculable a partir del recuento diferencial de leucocitos. El objetivo de este estudio es analizar el papel del INL en la detección de apendicetomías negativas, y comparar su utilidad con otros factores clínicos, ecográficos y de laboratorio previamente descritos. Métodos: Estudio retrospectivo en pacientes menores de 16 años con sospecha de apendicitis aguda intervenidos en nuestra institución entre 2017-2020, que fueron divididos en 2 grupos según hallazgos histológicos apendiculares: Grupo AN: apendicitis negativa; ausencia de inflamación y grupo AP: apendicitis positiva; presencia de inflamación en la pared apendicular. Se analizaron las características demográficas, clínicas, ecográficas y de laboratorio. Resultados: Se incluyeron 1.269 pacientes (1.244 en el grupo AP; 25 en el grupo AN), sin diferencias demográficas entre ellos. Los pacientes del grupo AN presentaron un porcentaje significativamente menor de náuseas y vómitos en comparación con el grupo AP (p < 0,001) y menor diámetro ecográfico apendicular (8,1 ± 2,1 vs. 9,7 ± 2,8 mm; p < 0,001). Los recuentos de leucocitos, neutrófilos e INL fueron significativamente superiores en el grupo AP (p < 0,001), así como la proteína C reactiva (18,6 vs. 2,6; p = 0,005). El análisis mediante curva ROC mostró que el INL fue el parámetro con mayor AUC (0,879) para el diagnóstico de apendicitis negativa, con un punto de corte de 2,65 con una sensibilidad del 84,2% y una especificidad del 83,8% máximas. Conclusiones: El INL es el parámetro preoperatorio que mejor distingue a los pacientes sin apendicitis aguda. Los valores inferiores a 2,65 deben hacernos sospechar otra causa diferente a la apendicitis.